(untitled) (International Journal of Food and Nutritional Sciences, 2023)
Vehicular Ad-hoc Networks (VANETs), which are a new emerging network technology derived from ad-hoc networks. In the field of Intelligent Transportation Systems (ITS), communications without a wire between vehicles (V2V) appear as an accident prevention solution offering a wider vision than conventional sensors. By linking vehicles to telecommunications network (V2I), new perspectives are offered both passengers and driver with conventional communication applications such as access Internet, e-learning, games or chat. This means that future mobile networks like VANETs will have to integrate communications, mobility, Quality of Service (QoS) and security. In this paper, we propose to contribute on how to improve security without degrading the quality of service QoS in a highly mobile environment as VANETs networks.